Peningkatan Hasil Belajar Bahasa Indonesia Materi Menulis Kata Dengan Media Gambar Kelas 2 SDN Kedaung Wetan 1 - Kurniati, Nia (Arfah BHMS Foundation, 2025)
This research was motivated by the low ability of students to write words when learning Indonesian. This is because teachers in teaching how to write do not use learning media that is interesting to students so it tends to be boring and seems monotonous. In connection with this, research was conducted using image media to improve students' word writing skills. This research aims to improve the ability of Class 2 students at SDN Kedaung Wetan 1 Tangerang City in writing words using image media. This research uses a Classroom Action Research design which is carried out in two cycles through the same stages, namely planning, implementation, observation and reflection. This research was carried out in Class 2 of SDN Kedaung Wetan 1 Tangerang City with a total of 27 students consisting of 16 male students and 11 female students. The data collection techniques used were observation and evaluation. The collected data was analyzed using qualitative and quantitative analysis techniques. The results of the research show that with image media, the results from cycle I to cycle II have increased. In the pre-cycle the average score obtained by students was 64.33 with a classical completion level of 45%, the incomplete score in cycle I was 55%, while in cycle II the average score obtained by students was 85.67 with the classical completeness level being 90%, resulting in an increase in classical completeness of 50%. These results can be concluded that the use of image media can improve the word writing ability of class 2 students at SDN Kedaung Wetan 1, Tangerang City